Little women - Alcott, Louisa May (Oxford University Press, 2000)
When Christmas comes for the four March girls, there is no money for expensive presents and they give away their Christmas breakfast to a poor family. But there are no happier girls in America than Meg, Jo, Beth, and Amy. They miss their father, of course, who is away at the Civil War, but they try hard to be good so that he will be proud of his 'little women' when he comes home. This heart-warming story of family life has been popular for more than a hundred years